Effects of Eurycoma longifolia on fracture healing of androgen-deficient osteoporosis model: a micro computed tomograph analysis - Azri J; Ahmad Nazrun Shuid; Sabarul Afian Mokhtar; Mohd Fadli K; Norliza Muhammad (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Micro computed tomography (micro-CT) imaging is a useful tool to monitor fracture healing in osteoporosis model. It creates a 3-D image of the fracture callus which can be analysed to assess bone parameters quantitatively. In this study, micro-CT was used to assess the fracture healing of orchidectomised rats, an androgen-deficient osteoporosis model. The effects of Eurycoma longifolia, a medicinal plant with pro-androgenic effects, on fracture healing were assessed. The rats were grouped into orchidectomised-control (ORX), sham-operated (SHAM), orchidectomised and injected with testosterone intramuscularly once weekly (TEN) and orchidectomised and daily oral gavage of Eurycoma longifolia (EL). Treatment duration was six weeks following bone fracture. Fracture was induced in the right tibia of all the rats. A total of 100 axial slices above and below fracture line were scanned with a micro-CT. The micro-CT analysis was able to detect significant difference in the fracture healing rate of ORX and TEN groups. The bridging cortices and fraction of mineralized tissue of the bridging cortices of the callous of ORX group was significantly lower than TEN group. No significant micro-CT changes were seen in the fracture healing of the EL group. The effect of EL on fracture healing was not demonstrable in orchidectomised rat model.